Morphological Feature Of Neutrophil As A Prognostic Indicator In Complicated Malaria - SATYAJIT BAGUDAI; SUDEEP SATPATHY (International Journal of Pharma and Bio Sciences, 2012)
Malaria carries a high degree of importance among the tropical diseases in India. Along with the research to develop newer diagnostic aid & treatment, the identification of new prognostic markers is also necessary for prediction of course & complication. The aim is to analyze the morphological changes of neutrophil in plasmodium falciparum malaria like the presence of hemozoin granule & study their prognostic implication. Seventy six adult & pediatric patients, presenting to the hospital over a period of one month with clinical features of malaria & positive for falciparum were studied. All cases were classified as complicated or not, according to WHO criteria. It was found that the neutrophilic hemozoin pigments were significantly associated with complicated pediatric patients (P < 0.01). There was no signification association (P>0.05) between hemozoin pigment & complicated adult cases. The mortality was also not associated with the presence of pigment in both pediatric & adult cases (P > 0.05) So it can be concluded that the presence of hemozoin pigment in neutrophil is significantly associated with more severity in pediatric falciparum malaria, and not significantly associated with mortality in both pediatric & adult falciparum malaria.